2012
DOI: 10.1139/g2012-004
|View full text |Cite
|
Sign up to set email alerts
|

Absence of linkage disequilibria between chromosomal arrangements and mtDNA haplotypes in natural populations ofDrosophila subobscurafrom the Balkan Peninsula

Abstract: The genetic structure of Drosophila subobscura from the Balkan Peninsula was studied with respect to restriction site polymorphism of mitochondrial DNA in populations from the Derventa River Gorge and Sicevo Gorge (Serbia). To investigate the role of cytonuclear interactions in shaping mitochondrial DNA variability in natural populations of this species, the study was complemented with the analysis of linkage disequilibria between mitochondrial haplotypes and chromosomal inversion arrangements. Similar to othe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 44 publications
0
20
0
Order By: Relevance
“…In this species, variation is ubiquitous and strikingly geographically homogenous, with two dominant mtDNA haplotypes (termed I and II) typically co- occurring within populations at stable frequencies of approximately 50:50, across both the new and the old world [9, 2228]. Moreover, experimental studies have shown that the two mtDNA haplotypes are not functionally equivalent: flies that harbor these haplotypes differ in major life history traits such as metabolic rate [29], fertility [30], viability, longevity and desiccation resistance [8, 31] and two earlier studies of laboratory cage populations were able to reject genetic drift as the sole mediator of mtDNA haplotype changes [9, 32].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this species, variation is ubiquitous and strikingly geographically homogenous, with two dominant mtDNA haplotypes (termed I and II) typically co- occurring within populations at stable frequencies of approximately 50:50, across both the new and the old world [9, 2228]. Moreover, experimental studies have shown that the two mtDNA haplotypes are not functionally equivalent: flies that harbor these haplotypes differ in major life history traits such as metabolic rate [29], fertility [30], viability, longevity and desiccation resistance [8, 31] and two earlier studies of laboratory cage populations were able to reject genetic drift as the sole mediator of mtDNA haplotype changes [9, 32].…”
Section: Resultsmentioning
confidence: 99%
“…We here note that linkage disequilibrium between mtDNA haplotypes and the nuclear genome, e.g. chromosomal inversions, is very low at most in D. subobscura [33, 38, 39], which is expected given the fact the two genomes do not cosegregate in males [17, 18]. …”
Section: Resultsmentioning
confidence: 99%
“…In G 0 , the inversions (or chromosomal arrangements) and karyotypes found are characteristic of the Avala mountain population (Zivanovic and Mestres 2010a) and also of the Balkan region (Zivanovic et al 1995(Zivanovic et al , 2002Zivanovic 2007;Rasic et al 2008;Stamenkovic-Radak et al 2008;Kenig et al 2010;Zivanovic and Mestres 2011;Jelić et al 2012). No significant changes between G 0 and G 12 were observed for the inversion and arrangement frequencies.…”
Section: Discussionmentioning
confidence: 93%
“…Linkage disequilibrium among mitochondrial haplotypes and chromosomal arrangements was tested separately in each population, and for the whole sample set according to Jelić et al (2012a, b) and Oliver et al (2002). D and D´ values were estimated (Lewontin, 1964).…”
Section: Analysis Of Linkage Disequilibrium (Ld) Between Mtdna and Inmentioning
confidence: 99%
“…Seasonal bottlenecks and population expansion are responsible for the excess of singleton mutations Christie et al, 2010). Considering the two most frequent haplotypes, selection possibly acts jointly on combinations of mitochondrial and nuclear alleles, and several studies have analysed the linkage disequilibrium (LD) between mitochondrial haplotypes and chromosomal inversions (Oliver et al, 2002;Jelić et al, 2012a, b). These studies show transient LD due to temporal and spatial differences in the action of ecologically specifi c selection pressures.…”
Section: Introductionmentioning
confidence: 99%